Use of isavuconazole in mucormycosis: a systematic review - Shobha Sanjeewani Gunathilaka; Reshani Kaumada Keragala; Kasun Madhumal Gunathilaka; Sujanthi Wickramage; Sachithra Ravindi Bandara; Indika Sanjeewa Senevirathne; Asela Sampath Jayaweera (BMC Infectious Diseases)
Abstract Background Mucormycosis is an opportunistic fungal infection which is associated with poor prognosis. Only a few antifungals are available in the arsenal against mucormycosis. The global guidelines for diagnosing and managing mucormycosis recommend high doses of liposomal amphotericin B (LAmB) as the first-line treatment. Isavuconazole is another potential treatment option for mucormycosis. Main body This systematic review aims to consolidate and analyse existing evidence concerning the efficacy and safety of isavuconazole in treating mucormycosis alone or in combination with LAmB. For data aggregation, comprehensive searches were conducted across various electronic databases, such as PubMed, Science Direct, Trip, Google Scholar, the Cochrane Library, and Open-Gray. Furthermore, we explored the gray literature, employing tailored keywords. The reference lists of the selected articles were scrutinized to identify additional pertinent publications. Articles reporting any studies, case series, or case reports on any form of mucormycosis exclusively involving human subjects published in English were included. There were no time restrictions involved. We extracted crucial data, such as publication year, country, disease form, isavuconazole dosage, frequency, duration, overall outcomes, and reported adverse effects. A total of 31 articles, which included four case series, 24 case reports, one open-label trial, one randomized controlled trial, and one non-interventional registry study, were included in the final analysis. 135 adult patients and 14 children were treated with isavuconazole as primary monotherapy, primary combination therapy, nonprimary monotherapy, or nonprimary combination therapy. The mortality rate following LAmB monotherapy, amphotericin B plus azole, amphotericin B followed with azole, posaconazole only and isavuconazole only was 32%, 6.6%, 13.7%, 17.2% and 24.6%, respectively. The heterogeneity of the studies did not allow for a comparison of the different treatment strategies (primary mono- vs. primary combination, etc.). Short conclusion The use of isavuconazole in combination therapies during the acute phase via intravenous administration alongside LAmB or other triazoles, followed by long-term monotherapy via the oral route, has yielded promising recovery rates. Adverse events associated with the use of isavuconazole are infrequently reported.